Synthesis of Silver Nanoparticles Using a Novel Cyanobacteria Desertifilum sp. extract: Their Antibacterial and Cytotoxicity Effects - Hamida RS (Dove Medical Press, 2020)
Reham Samir Hamida, 1 Nabila Elsayed Abdelmeguid, 1 Mohamed Abdelaal Ali, 2 Mashael Mohammed Bin-Meferij, 3 Mahmoud Ibrahim Khalil 4 1Molecular Biology Unit, Department of Zoology, Faculty of Science, Alexandria University, Alexandria, Egypt; 2Biotechnology Unit, Department of Plant Production, College of Food and Agriculture Science, King Saud University, Riyadh, Saudi Arabia; 3Department of Biology, College of Science Princess Nourah bint Abdulrahman University, Riyadh, Saudi Arabia; 4Department of Biological Sciences, Faculty of Science, Beirut Arab University, Beirut, LebanonCorrespondence: Mashael Mohammed Bin-Meferij; Mahmoud Ibrahim Khalil Tel +961 81982014Email mmbinmufayrij@pnu.edu.sa; m.khalil@bau.edu.lbBackground: The emergence of multi drug-resistant (MDR) bacterial infections and cancer has necessitated the development and discovery of alternative eco-safe antibacterial and anticancer agents. Biogenic fabrication of metallic nanoparticles is an emerging discipline for production of nanoproducts that exert potent anticancer and antibacterial activity, and do not suffer from the limitations inherent in physiochemical synthesis methods.Methodology: In this study, we isolated, purified, and characterized a novel cyanobacteria extract (Desertifilum IPPAS B-1220) to utilize in biofabrication of silver nanoparticles (D-SNPs). D-SNPs were produced by adding Desertifilum extract to silver nitrate solution under controlled conditions. Biofabrication of D-SNPs was confirmed using a UV-Vis spectrophotometer. The resultant D-SNPs were characterized using XRD, FTIR, SEM, and TEM. The toxicity of D-SNPs against five pathogenic bacteria and three cancer cell lines (MCF-7, HepG2, and Caco-2) was evaluated.Results: Formation of D-SNPs was indicated by a color change from pale yellow to dark brown. The peak of the surface plasmon resonance of the D-SNPs was at 421 nm. The XRD detected the crystallinity of D-SNPs. FTIR showed that polysaccharides and proteins may have contributed to the biofabrication of D-SNPs. Under SEM and TEM, the D-SNPs were spherical with diameter ranges from 4.5 to 26 nm. The D-SNPs significantly suppressed the growth of five pathogenic bacteria, and exerted cytotoxic effects against MCF-7, HepG2, and Caco-2 cancer cells with IC 50 values of 58, 32, and 90 μg/mL, respectively.Conclusion: These findings showed for the first time the potentiality of novel cyanobacteria strain Desertifilum IPPAS B-1220 to fabricate small SNPs that acted as potent anticancer and antibacterial material against different cancer cell lines and pathogenic bacterial strains. These findings encourage the researchers to focus on cyanobacteria in general and especially Desertifilum sp. IPPAS B-1220 for synthesizing different NPs that opening the window for new applications.Keywords: nanotechnology, eco-friendly, D-SNPs, physicochemical, cytotoxic activity